Decentralized Virtual Impedance-based Circulating Current Suppression Control for Islanded Microgrids - Abu Bakar, A.; Pathan, E.; Khan, M. K.; Sadiq, M. A.; Rabani, M. I.; Goli, S. B.; Pathan, F.; Shaikh, M. A. (Engineering, Technology & Applied Science Research, 2021)
Parallel connected inverters in islanded mode, are getting momentous attention due to their ability to increase the power distribution and reliability of a power system. When there are different ratings of Distributed Generation (DG) units, they will operate in parallel connection due to different output voltages, impedance mismatch, or different phase that can cause current to flow between DG units. The magnitude of this circulating current sometimes can be very large and damage the DG inverters and also cause power losses that affect power-sharing accuracy, power quality, and the efficiency of the Microgrid (MG) system. Droop control, improved droop control, and virtual impedance control techniques and modifications in the virtual impedance control technique are widely used to suppress the circulating current. However, the addition of the virtual impedance to each inverter to compensate the output impedance is resistive or inductive in nature. The resistive nature of the output impedance always causes a certain voltage drop, whereas the inductive nature of the output impedance causes phase delay for the output voltage. Both problems are addressed by the proposed control mechanism in this paper. Negative resistance, along with virtual impedance, is utilized in the proposed control strategy. The output impedance is to be maintained as inductive in nature to achieve good load sharing in droop control MGs. The simulation results validate the proposed control scheme.